City of Wind: Exposing the Invisible - Adamek, Kimberley (University of Waterloo, 2016)
Strong winds have breached the city walls. A set of iron chairs launch toward a couple passing an outdoor patio. Bags of groceries fling from unsuspecting hands and scatter across the sidewalk. A group of cyclists swerve onto a busy road as they pass a newly constructed tower. Pedestrians are experiencing these disruptive wind-related events as a result of the increase in tall building construction and its unavoidable interactions with wind. Enclosures that provide controlled environments are unintentionally encouraging winds that challenge pedestrian safety and comfort at grade. With few visual guidelines and tools accessible to them, designers are not only limited in their ability to understand architectural aerodynamics but also lack the knowledge to properly make use of available modes of software and testing. While other elements of design such as daylighting, can be verified through sight, the invisibility of wind makes deciphering its effects a difficult and perpetual task. This thesis offers insight on how and where to look for wind — not to “see” in the traditional sense, but to look beneath the surface of things. An exploration of architectural aerodynamics is visually represented and organized in three interrelated parts: Drawing the Wind, Laws of Motion, and Parameters of Prediction. The first is a historical overview of humanity’s relationship with wind, the second a documentation of architectural aerodynamic principles, effects and methods of simulation, while the final is a visual exploration of the link between buildings and wind sited in Toronto, Ontario. Each part is a visual exploration in, and reflection of, environmental awareness. By using visualization methods to improve the communication between designers and wind specialists, this document promotes a design practice that enables a productive consideration of wind in the city. Ultimately, designers must be aware of basic aerodynamic principles and the corresponding effects to not only provide optimal interior environments within buildings, but also in between them.
Keywords: Wind; Architectural Aerodynamics; Wind Tunnel